The Relationship of Gadget Use Behavior on Sleep Disorders in Children of SDN 1 Jlamprang, Leksono District, Wonosobo Regency - Bacharuddin, Rizqi; Ernawati, E; Saraswati, Rina (Prosiding University Research Colloquium, 2022)
Background : Sleep disorders are defined as unsatisfactory sleep patterns for everyone characterized by disturbances in the amount, quality or time of sleep in an individual. One of the factors of sleep disturbance in students is the use of gadgets. Gadgets are electronic devices that are often used to make it easier for users to carry out activities according to their needs. The level of use of gadgets in students can trigger addiction in using gadgets. Related to this, researchers are interested in conducting research on the relationship between gadget use behavior and sleep patterns in children at SDN 1 Jlamprang, Leksono District, Wonosobo Regency. Research Objectives : To determine the relationship between gadget use behavior and sleep patterns in children at SDN 1 Jlamprang, Leksono District, Wonosobo Regency . Research Methods : This was a non-experimental quantitative study using a cross-sectional approach to 77 respondents. The instrument used was a smartphone addiction questionnaire. and SDSC with research analysis using Sperman rank. Research Results : The results of the statistical test ofcorrelation sperman rank obtained p value = 0.00 with a significance of 0.05, with this Ho is rejected, Ha is accepted, which means that there is a relationship between the behavior of using gadgets on the sleep patterns of SDN 1 Jlamprang children, Leksnono District, Wonosobo Regency. Correlation coefficient (?=0.615). Recommendations for further research : It is hoped that further research can add a child's growth variable to the effect of using gadgets on children.